2022
DOI: 10.1186/s40643-022-00502-w
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic synthesis of a novel solid–liquid phase change energy storage material based on levulinic acid and 1,4-butanediol

Abstract: The current energy crisis has prompted the development and utilization of renewable energy and energy storage material. In this study, levulinic acid (LA) and 1,4-butanediol (BDO) were used to synthesize a novel levulinic acid 1,4-butanediol ester (LBE) by both enzymatic and chemical methods. The enzymatic method exhibited excellent performance during the synthesis process, and resulted in 87.33% of LBE yield, while the chemical method caused more by-products and higher energy consumption. What’s more, the the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Alkyl levulinates can be produced via the alcoholysis of sugar monomers or LA esterification [7,8,22]. The latter route can be done via homogenous [23], heterogeneous [24][25][26][27][28][29][30] or enzymatic catalysis [31][32][33][34][35][36][37]. The use of heterogeneous catalysts such as resins, zeolite or immobilized enzymes should be favored to avoid additional separation stages [23].…”
Section: Introductionmentioning
confidence: 99%
“…Alkyl levulinates can be produced via the alcoholysis of sugar monomers or LA esterification [7,8,22]. The latter route can be done via homogenous [23], heterogeneous [24][25][26][27][28][29][30] or enzymatic catalysis [31][32][33][34][35][36][37]. The use of heterogeneous catalysts such as resins, zeolite or immobilized enzymes should be favored to avoid additional separation stages [23].…”
Section: Introductionmentioning
confidence: 99%
“…However, few works have used enzymatic treatments in the preparation of phase-change materials. Zhai et al [ 52 ] pointed out that the enzymatic method exhibited excellent performance during the synthesis process, while the chemical method caused more by-products and higher energy consumption.…”
Section: Resultsmentioning
confidence: 99%
“…20 Additionally, the product yields could be suppressed with increasing reactant concentration or reaction temperature. 21,22 In the aspect of catalysts for production of HMF, several research groups reported novel catalysts that yielded a high percentage of conversion of biomass to HMF. Malkar et al reported an aluminum-exchanged heteropolyacid with the maximum conversion of 99% biomass to HMF within 10 h. This four-time reusable catalyst was stable and able to form C9 adducts at up to 84%.…”
Section: Introductionmentioning
confidence: 99%
“…However, the biocatalytic process generally requires a high production cost and a limited range of operating conditions . Additionally, the product yields could be suppressed with increasing reactant concentration or reaction temperature. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation